Enhanced Anaerobic Degradation Of Palm Oil Mill Effluent Using Butyrate, Cao-Ckd And Denitrifying Sulfide Removal - Rumana, Ghufran (2012)
During this research three experiments were performed. In the first experiment Palm oil Mill Effluent (POME) with concentrated butyrate was treated in a 4.5 L upflow anaerobic sludge blanket reactor (UASBR), run over a range of influent concentrations (16.5-46.0 g-COD L-1), chemical oxygen demand (COD) loading rates (1.5-11.5 g CODL-1 d-1) and 11-4 days hydraulic retention time (HRT) at 37 °C by maintaining pH between 6.5-7.5. The process consistently removed 9799% of COD at loading rates up to 1.5-4.8 g COD L -1 d -1 by varying HRT (11-7.2 days). The conversion of acetate to methane appeared to be rate limiting step. Maximum biogas (20.17 LL -1 d -1) and methane production (16.2 LL) were obtained at COD loading rate of 4.80 gL -1 d -1 and HRT of 7.2 days. The biogas and methane production were higher in the presence of butyrate compared to control. The methane content of the biogas was in the range of 70-80% throughout the study while in control it was 60-65%. Finding of this study clearly indicates the succesful treatment of POME with butyrate in UASBR. In the second experiment, calcium oxide-cement kiln dust (CaO-CKD) was used to enhance the granulation process. The granulation process in POME using CaO-CKD provided an attractive and cost effective treatment option. In this study the efficiency of CaOCKD at doses of 1.5 to 20 gL -1 was tested in batch experiments and found that 10 g of CaO/L caused the greatest degradation of VFA, butyrate and acetate. An upflow anaerobic sludge blanket (UASB) reactor was operated continuously at 35 ºC for 150 days to investigate the effect of CaO-CKD on sludge granulation and methanogenesis during start-up. The treatment of POME emphasized the influence of varying organic loading rates (OLR). Up to 94.9% of COD was removed when the reactor was fed with the 15.5 to 65.5 g-COD gL at an OLR of 4.5-12.5 Kg-CODm-3 d -1, suggesting the feasibility of using CaO in an UASB process to treat POME. The ratio of volatile solids/total solids (VS/TS) and volatile fatty acids in the anaerobic sludge in the UASB reactor decreased significantly after long-term operation due to the precipitation of calcium carbonate in the granules. Granulation and methanogenesis decreased with an increase in the influent CaO-CKD concentration. In the third experiment, the inhibitory effects of 134.82-771.9 mgL -1 d -1 of sulfide loading rate (SLR) and 58.79-337.56 mgL -1 d -1 -1 of nitrate loading rate (NLR) on methanogenesis were investigated in a mixed methanogenic culture using butyrate as carbon source. A novel strategy was adopted to cultivate mature granules using anaerobic sludge of palm oil mill effluent (POME) as seed sludge, incubated in DSR medium to acclimate the denitrifiers. Biological denitrification was used to eliminate carbon, nitrogen and sulfur in an anaerobic granular bed reactor (AGBR) of 4.5 L by varying hydraulic retention time from 35.6-6.2 days. The maximum nitrate and sulfide removal efficiencies were observed up to SLR and NLR of 188.42 mgL -1 d -1 and 82.39 mgL -1 d -1 respectively. Maximum VFA removal of 82% was obtained on SLR and NLR of 230 mgL -1 d -1 and 100.62 mgL -1 d-1.